Climate-Based Suitability Assessment for Methane Mitigation by Water Saving Technology in Paddy Fields of the Central Plain of Thailand - Prangbang, Punyaporn; Yagi, Kazuyuki; Aunario, Jorrel Khalil S.; Sander, Bjoern Ole; Wassmann, Reiner; Jäkel, Thomas; Buddaboon, Chitnucha; Chidthaisong, Amnat; Towprayoon, Sirintornthep (Frontiers in Sustainable Food Systems, 2020)
The alternate wetting and drying (AWD) water management technique has been identified as one of the most promising options for mitigating methane (CH4) emissions from rice cultivation. By the nature of this approach, however, this option will be limited to paddy fields where farmers have sustained access to irrigation water. In addition, the paddy fields should also fall dry once irrigation is stopped which can be impaired by heavy rainfall. Therefore, it is necessary to understand the specific conditions and suitability of an area in which AWD is foreseen to be applied for assessing CH4 mitigation potential in view of planning regional and national mitigation actions. In this study, we applied a methodology developed for assessing climatic suitability of AWD to the paddy fields in the central plain of Thailand in order to determine potential spatial and temporal boundaries given by climatic and soil parameters that could impact on the applicability of AWD. Related to that, we also assessed the CH4 mitigation potential in the target provinces. The results showed that the entire area of six target provinces was assessed to be climatically suitable for applying AWD in both the major and second rice seasons. A sensitivity analysis to account for uncertainties in soil percolation and suitability classification indicated that these settings did not affect the results of this suitability assessment, although they changed the distribution of moderate and high climatic suitability area in the major rice season to some extent. Following the methodologies of the IPCC Guidelines, we estimated that the AWD scenario reduced annual CH4 emissions by 45% compared with the emissions in the baseline (continuously flooded) scenario. The potential of CH4 emission reduction by implementing AWD was estimated to be 84,900 t CH4 year-1, equivalent to 2.38 Mt CO2-eq year-1, in the target provinces. However, we recognize the possibility that other parameters not included in our current approach may significantly influence suitability of AWD and propose areas for further improvements derived from these limitations. All in all, we think our results will be instrumental in guiding practitioners at all levels involved in water management for rice cultivation.